On the Positional Distribution of an Armenian Auxiliary: Second‐Position Clisis, Focus, and Phases. (16th January 2017) - Kahnemuyipour, Arsalan; Megerdoomian, Karine
Abstract: This paper investigates the positional distribution of an auxiliary clitic in Eastern Armenian in informationally marked sentences. The paper builds on previous work on the distribution of the auxiliary in focus‐neutral contexts (Kahnemuyipour & Megerdoomian 2011), where its placement was analyzed as second position within the lower phase domain (or vP), thereby extending the inventory of known second‐position phenomena from the clause to the smaller verbal domain. To account for the distribution of the auxiliary in sentences with focused constituents, it is proposed here that the relevant phase in this context is the Focus Phrase, with the auxiliary appearing in the expected second position. This falls into place under a dynamic view of phasehood that defines the phase as the highest projection of a lexical category and takes low focus to be part of the verbal domain and its corresponding phase (Bošković 2014). These proposals rely highly on the parallelism between clausal and verbal domains both in terms of their status as phases as well as their structural makeup. To the extent that these proposals succeed in accounting for the facts we discuss, they provide further evidence for the dynamic conception of phases as well as the CP–vP parallelism.